Effect of Single High-Dose Vitamin D3 Supplementation on Post-Ultra Mountain Running Heart Damage and Iron Metabolism Changes: A Double-Blind Randomized Controlled Trial - Stankiewicz, Błażej; Mieszkowski, Jan; Kochanowicz, Andrzej; Brzezińska, Paulina; Niespodziński, Bartłomiej; Kowalik, Tomasz; Waldziński, Tomasz; Kowalski, Konrad; Borkowska, Andżelika; Reczkowicz, Joanna; Daniłowicz-Szymanowicz, Ludmiła; Antosiewicz, Jędrzej (Nutrients, 2024)
Exercise-induced inflammation can influence iron metabolism. Conversely, the effects of vitamin D3, which possesses anti-inflammatory properties, on ultramarathon-induced heart damage and changes in iron metabolism have not been investigated. Thirty-five healthy long-distance semi-amateur runners were divided into two groups: one group received 150,000 IU of vitamin D3 24 h prior to a race (n = 16), while the other group received a placebo (n = 19). Serum iron, hepcidin (HPC), ferritin (FER), erythroferrone (ERFE), erythropoietin (EPO), neopterin (NPT), and cardiac troponin T (cTnT) levels were assessed. A considerable effect of ultramarathon running on all examined biochemical markers was observed, with a significant rise in serum levels of ERFE, EPO, HPC, NPT, and cTnT detected immediately post-race, irrespective of the group factor. Vitamin D3 supplementation showed a notable interaction with the UM, specifically in EPO and cTnT, with no other additional changes in the other analysed markers. In addition to the correlation between baseline FER and post-run ERFE, HPC was modified by vitamin D. The ultramarathon significantly influenced the EPO/ERFE/HPC axis; however, a single substantial dose of vitamin D3 had an effect only on EPO, which was associated with the lower heart damage marker cTnT after the run.
Keywords: železo; troponin T; ultramarathon; Humans; Iron; lidé středního věku; erythropoetin; nemoci srdce; Double-Blind Method; cholekalciferol; Female; dospělí; hepcidiny; lidé; dvojitá slepá metoda; Biomarkers; Erythropoietin; erythropoietin; Hepcidins; Cholecalciferol; Adult; ženské pohlaví; biologické markery; Male; ferritin; Middle Aged; iron; potravní doplňky; maratonský běh; Dietary Supplements; Troponin T; Marathon Running; mužské pohlaví; vitamin D; erythroferrone; Heart Diseases